HBV 2021: New therapeutic strategies against an old foe. (21st June 2021) - Roca Suarez, Armando Andres; Testoni, Barbara; Zoulim, Fabien
Abstract: Hepatitis B virus (HBV) affects more than 250 million people worldwide, and is one of the major aetiologies for the development of cirrhosis and hepatocellular carcinoma (HCC). In spite of universal vaccination programs, HBV infection is still a public health problem, and the limited number of available therapeutic approaches complicates the clinical management of these patients. Thus, HBV infection remains an unmet medical need that requires a continuous effort to develop new individual molecules, treatment combinations and even completely novel therapeutic strategies to achieve the goal of HBV elimination. The following review provides an overview of the current situation in chronic HBV infection, with an analysis of the scientific rationale of certain clinical interventions and, more importantly, explores the most recent developments in the field of HBV drug discovery.